2019
DOI: 10.1038/s41598-019-52547-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Roses (Rosa hybrida L. ‘Herbert Stevens’) to Foliar Application of Polyamines on Root Development, Flowering, Photosynthetic Pigments, Antioxidant Enzymes Activity and NPK

Abstract: The effect of foliar application of polyamines on roses (Rosa hybrida cv. ‘Herbert Stevens’) was investigated in a factorial experiment based on a completely randomized design with three replications in a greenhouse. Two factors were applied including polyamine type (putrescine, spermidine, and spermine) and polyamine concentration (0, 1, 2 and 4 mM). The recorded traits included root fresh and dry weight, root length, number of flowers, flower longevity, chlorophyll content, carotenoids, antioxidant enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…Several studies have shown that the accumulation of ethylene can be influenced by plant resistance increasing substances [10,46]. Additionally, ethylene production in fruits has previously been shown to be inhibited by applications of PAs and having controversial effects on a number of physiological processes [46,47]. There is increasing evidence that PAs, whether applied exogenously, can positively affect plant growth, productivity, and heat as well drought stress tolerance [37], but there is no data on how they can affect ethylene emission in cold and freezing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that the accumulation of ethylene can be influenced by plant resistance increasing substances [10,46]. Additionally, ethylene production in fruits has previously been shown to be inhibited by applications of PAs and having controversial effects on a number of physiological processes [46,47]. There is increasing evidence that PAs, whether applied exogenously, can positively affect plant growth, productivity, and heat as well drought stress tolerance [37], but there is no data on how they can affect ethylene emission in cold and freezing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Each group consisted of 24 pots with 9 plants in each pot. PA concentration used in this study was chosen based on the other studies [47]. Three groups were…”
Section: Application Of Pasmentioning
confidence: 99%
See 2 more Smart Citations
“…47 The applications of various metabolites such as lactic acid, amino acids, and polyamines have been studied and reported thoroughly through the era of "green revolution" in the development of agricultural biotechnology due to their promotion to the plant growth. [48][49][50][51][52] It is worth mentioning that plant hormones and their analogues have also been widely used for growth regulation as either fertilizers or herbicides. [53][54][55][56][57][58][59][60][61][62][63] Nucleic acids and proteins can be regarded as metabolites as well, though they are usually studied individually due to their significance to plant metabolism.…”
Section: Metabolitesmentioning
confidence: 99%